(untitled) (Journal of Universal Excellence, 2026)
(RQ): What factors influence on motivation for adult learning? Purpose: The purpose and goal of the research is to examine and present education, social aspects of education, the impact of heredity and environment as a factor in motivating for education, and what motivates adults for education. Method: The method that we will use will be a qualitative, descriptive approach based on the study of existing literature, articles, and personal experiences. Results: The results showed that the development of the individual and society an important continuing education, which is related to the acquisition of knowledge, which can be used in various fields of life. Organization: Continuing adult education is important for personal and social development. Originality: Acquiring new knowledge is crucial for the effectiveness of an individual in different spheres of life. Limitations: The study was made on the basis of theories, articles and study tasks.